Mobilization protocol and early postoperative weight-bearing in transyndesmal ankle fractures - Yearson, Diego; Melendez, Ignacio; Anain, Federico; Siniscalchi, Santiago; Drago, Juan (Journal of the Foot & Ankle, 2021)
Objective: To disseminate a rehabilitation protocol with early mobilization and ambulation, with no external supports, reducing the time until full weight-bearing and providing greater postoperative comfort. Methods: We prospectively assessed a series of 68 patients, with level of evidence IV, mean age of 33.3 years. We performed open reduction with ankle lateral approach (Kocher) and internal fixation with an interfragmentary compression screw and a one-third locked tubular plate for neutralization. All patients were subjected to a rehabilitation protocol with early mobilization and weight-bearing. Results: No fracture displacements were observed on the postoperative radiographic controls, neither loosening nor ruptures of implants. There was no need to change rehabilitation guidelines either due to pain or to other subjective limitation. Conclusion: We can state that early joint mobilization and controlled progressive support, with appropriate osteosynthesis, resulting in an early return to everyday activities, both work and sports ones. Level of Evidence IV; Therapeutic Studies; Case Series.